Analysis of ablation areas in Antarctica through remote sensing - Traversa, Giacomo (Università degli Studi di Siena, 2023)
The PhD thesis intends to study and map those areas in Antarctica involved in surficial ablation processes linked to the wind action (wind-scouring phenomenon, i.e., erosion and sublimation of snow and ice for the effect of katabatic winds). In fact, Antarctica shows a meanly positive mass balance and the analysis of ablation areas, which can show near-zero or negative surface mass balance in the case of glazed snow and blue ice respectively, becomes fundamental since an eventual expansion would have consequences also on continental mass balance, leading to effects on sea-level rise. To glazed snow and blue ice, the study of snow megadunes is added, since these landforms are associated to the presence of glazed snow (characterizing their leeward flanks) and they present m/km variations leading to impacts on snow accumulation processes. All these surfaces and landforms optically behave differently to surrounding snow, the main surface of Antarctica, showing a lower albedo and so can be investigated from the space. Therefore, remote sensing, i.e., the study of globes through satellite imagery, has a key role in this research project and allows mapping and temporal-spatial analyses of these areas. Albedo was analysed using both already available data of Moderate Resolution Imaging Spectroradiometer (MODIS) and data that needed different calibration steps, i.e., Landsat-mission imagery. In the second case, a new model for its calculation was validated for broadband albedo and is under evaluation for narrowband albedo. MODIS was used for determining blue ice optical properties, which show an albedo of 0.50-0.70 and Landsat instead was applied in snow-glazed analyses, as its higher spatial resolution allowed to detect the slightly lower albedo that these surfaces have in respect to surrounding snow (maximum -0.04 in near-infrared wavelengths). Additionally, the other investigated meteorological parameters were wind, which can be studied using reanalysis atmospheric models or using a model derived from sastrugi ...